INNOVATIVE MANAGEMENT IN HIGHER EDUCATION: ASSESSING STRATEGIES AND IMPACTS - Gafurova, Dilshoda (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The evolving landscape of higher education demands a shift from traditional administrative frameworks to innovative management practices. As Higher Education Institutions (HEIs) strive to remain relevant in a rapidly changing world, the integration of innovative strategies becomes paramount. This article offers a comprehensive assessment of these novel management practices, emphasizing their role in enhancing educational outcomes, fostering research, and ensuring institutional agility. Through a systematic evaluation, the article sheds light on the challenges, benefits, and transformative potential of innovative management in HEIs.